Role of pragmatic potential of phraseological units in the realization of cognitive models of situations - А. А. Asabina (Вестник Самарского университета: История, педагогика, филология, 2022)
This article is devoted to the study of the role of pragmatic potential of phraseological units in the realization of cognitive models of situations. The timeliness of this work consists in the absence at the moment of information about the components of cognitive models of situations that can be most effectively used by the authors of articles to realize their pragmatic intentions through the pragmatic potential of phraseological units. The purpose of the study is to determine the components of cognitive models of situations that are actualized and brought to the fore through the pragmatics of phraseological units in the texts of the English-language media discourse, the reasons for the actualization of precisely these components of cognitive models of situations, as well as to establish what pragmatic goals of the authors this is due. To achieve it, the author has set the following tasks: sampling phraseological units from the English-language media discourse, drawing up schemes of cognitive models of situations, determining which component of the cognitive model is actualized with the help of a phraseological unit. The material for the analysis was articles from the British newspaper The Times dated May 22, 2021. The author of the article uses various methods: descriptive, contextual analysis, comparative, methods of observation, content analysis and discourse analysis. The study uses the linguistic concept of T.A. Van Dijk, which includes the analysis of the cognitive model of the situation and the allocation of its individual components: participants, their actions, circumstances and other components were identified. The analysis made it possible to identify the component action of cognitive models, which in most examples is brought to the fore through the pragmatics of FE, as well as to determine the cause of this phenomenon.